Respuesta :
Answer:
The ratio is 6 : 1
Explanation:
To find the ratio, we first need to make the units consistent.
I will convert all units to "months"
we know that one year has 12 months, therefore:
3 years = 3 * 12 = 36 months
6 months is simply equal to 6 months
Now, to get the ratio, we will simply divide the two quantities and simplify as follows:
36 months to 6 months = [tex] \frac{36 months}{6months} [/tex] = [tex] \frac{36}{6} [/tex] = [tex] \frac{6}{1} [/tex]
Based on the above, the ratio is 6:1
Hope this helps :)
The ratio is 6 : 1
Explanation:
To find the ratio, we first need to make the units consistent.
I will convert all units to "months"
we know that one year has 12 months, therefore:
3 years = 3 * 12 = 36 months
6 months is simply equal to 6 months
Now, to get the ratio, we will simply divide the two quantities and simplify as follows:
36 months to 6 months = [tex] \frac{36 months}{6months} [/tex] = [tex] \frac{36}{6} [/tex] = [tex] \frac{6}{1} [/tex]
Based on the above, the ratio is 6:1
Hope this helps :)
Answer: The simplest form of the ratio is 6 : 1.
Step-by-step explanation: We are given to write a ratio in simplest form that compares the the following two quantities:
3 years to 6 months.
We know that
[tex]\textup{1 year}=\textup{12 months}.\\\\\therefore \textup{3 years}=12\times 3=36~\textup{months}.[/tex]
Therefore, the required ratio is
[tex]36~\textup{months}:6~\textup{months}\\\\=\dfrac{36}{6}\\\\\\=\dfrac{6}{1}\\\\\\=6:1.[/tex]
Thus, the simplest form of the ratio is 6 : 1.